An exponential representation for some integrals with respect to Lebesgue-Poisson measure - Rebenko, A. L.; Boluh, V. A. (Methods of Functional Analysis and Topology, 2014)
We prove a theorem that allows to simplify some combinatorial calculations. An example of application of this theorem in statistical mechanics is given.